Is the full sternotomy in cardiac surgery still the preferred approach? - Tamer El Banna; Mohamed Makram; Ahmed Zayed (Journal of Medicine in Scientific Research, 2021)
Background There is increasing interest and patient demand for minimally invasive cardiac surgery. Aim We aimed to assess the safety and possibilities of such techniques and debated whether it would become the standard procedure. Patients and methods Since February 2013 till June 2019, 696 patients underwent variations of cardiac surgery procedures; of them, 456 patients underwent thoracoscopic minimally invasive mitral and tricuspid valve surgery; 65 patients underwent double valve replacement, and of them, 17 underwent concomitant tricuspid valve repair through upper mini-sternotomy; 88 patients underwent aortic valve replacement through upper mini-sternotomy; five cases underwent Bentall procedure through upper mini-sternotomy; five cases underwent atrial septal defect closure via thoracoscopic right mini-thoracotomy; three cases underwent excision of left atrial myxoma; one case underwent concomitant thoracoscopic mitral valve replacement and coronary artery bypass grafting; and 73 cases underwent coronary artery bypass grafting via right submammary incision, and of them 10 cases underwent hybrid technique. Results The procedure was successfully performed in all. Conversion rate to full sternotomy was 0% and to mini-thoracotomy procedure was 10 (1.4%) patients. Hospital mortality was seen in four (0.5%) patients, re-exploration for bleeding was done in four (0.5%) patients, and superficial wound infection was seen in 20 (2.8%) patients. Graft failure occurred in one patient who needed redo-operation, and one patient needed to lengthen the Left Internal Thoracic Artery (LIMA) with a composite vein graft. Conclusion Thoracoscopic minimally invasive mitral valve surgery and limited sternotomy incisions can be performed safely but definitely requires a learning curve. Good results and a high patient satisfaction are guaranteed. There is increased patient demand and popularity for such techniques in Egypt. Patient selection at the start of the program is essential. The progress is more rapid and promising, and by the end of this decade, there is strong possibility of becoming the standard procedure in cardiac surgery.